Edukasi Penyakit Tuberkulosis Paru pada Mahasiswa Vokasi Dilihat dari Aspek Pemeriksaan Radiologi dan Pengobatannya - Utami, Rose Malinda Andamari Wahyu; Utami, Lucky Restyanti Wahyu; Utomo, Slamet; Damayanti, Ferina (Universitas Muria Kudus, 2024)
The aim of the education carried out for vocational students at Widya Husada University Semarang is to increase understanding regarding radiological examinations which are used to diagnose pulmonary tuberculosis and the treatment efforts that can be given to sufferers. Based on the data obtained, it is known that the level of understanding of vocational students regarding radiological examinations carried out before and after treatment for pulmonary tuberculosis has a percentage of 84% and the level of understanding regarding treatment of pulmonary tuberculosis which must be started from the beginning in patients who forget to take medication has a percentage of 100%.